Geochemistry and Genesis of Late Paleoproterozoic Banded Iron Formations and Metamorphosed Chemical Precipitates Spatially Associated with Pb-Zn Broken Hill-type Mineralization near the Broken Hill Deposit, Curnamona Province, Australia - Serna, Erica (East Carolina University, 2014)
Banded and massive iron formations (IFs) and garnet- and gahnite-quartz rocks are spatially associated with the giant, late Paleoproterozoic, Pb-Zn-Ag Broken Hill sulfide deposit and hundreds of minor Broken Hill-type deposits in the southern Curnamona Province, Australia. The sulfide deposits, host rocks, and a variety of chemical precipitates that include IFs and garnet- and gahnite-rich rocks have been metamorphosed to the granulite facies. The IFs are found above, below, and along strike with the ore deposits and are among the youngest IFs that formed in the late Paleoproterozoic at ~ 1.69 Ga, after the Great Oxidation Event (GOE; ~2.35 Ga). Here the petrology and geochemistry of banded and massive IFs and garnet- and gahnite-quartz rocks from near the Broken Hill, Little Broken Hill, Wild Dog, Pinnacles, and Nine Mile Pb-Zn-Ag sulfide deposits is investigated to determine the genesis of the rocks and the physicochemical conditions of the fluids in the intracontinental Broken Hill rift basin at ~1.69 Ga, and ultimately the redox state of the water in this basin at the time of deposition. Banded and massive IFs mainly consist of magnetite-hematite, quartz, and ± garnet, while the rocks from Nine Mile consist of garnet and quartz, and gahnite and quartz. Bulk-rock major and trace element compositions show that the rocks are enriched in Si and Fe with moderate but variable amounts of Mn and Al, which reflect variations of hydrothermal (up to 80%) and detrital contribution in the precursor phases. The rocks formed as a mixture of Fe or Fe-Mn oxyhydroxides and minor clays similar to sediments from the modern redox-stratified rift basin at the Red Sea. Post-Archean Australian Shale (PAAS) normalized rare-earth element (REE) patterns of banded and massive IFs and garnet-quartz rocks exhibit a variety of REE contents and signatures with absent, very small, and moderately strong positive Eu anomalies suggesting that the precursor minerals formed from source hydrothermal fluids of variable temperatures. Strong positive Eu anomalies reflect source fluids with T > 250 °C and are associated with Mn-rich compositions that favor the incorporation of Eu. Small Eu anomalies reflect dilution by the addition of detritus, whereas strong negative Eu anomalies in gahnite-quartz rocks from Nine Mile likely reflect the discrimination of Eu by Fe-rich minerals in the precursor phases. Bulk-rock PAAS-normalized REE patterns range from flat, to light-REE (LREE) enriched, and slightly heavy-REE enriched, which reflect an oxygen-stratified water body. True negative Ce anomalies are only present in a few Mn-bearing banded IFs that have flat REE patterns and slightly higher Al contents than the rest, which reflects precipitation from relatively shallow and oxygenated water. Most rocks lack Ce anomalies, have variable LREE trends, some have LREE enrichment, and are Al-poor and Fe-rich, reflecting precipitation under suboxic conditions from deeper water than the other IFs, the existence of a redoxcline, and reductive dissolution of Fe-Mn oxyhydroxides that provided additional LREEs. Overall, the variety of REE patterns and LREE enrichment and the negative and absent Ce anomalies suggest that at ~ 1.7 Ga the water column in the intracontinental Broken Hill rift basin was stratified and supported the existence of an oxide shuttle that cycled LREEs, which is consistent with results from IFs of similar ages in other basins.
2017-06-04
Keywords: Geochemistry; Geology; Petrology; Banded iron formations; Precambrian; Rock-forming minerals--Australia; Metamorphic rocks--Australia; Quartz--Australia; Magnetite--Australia; Hematite--Australia